2018
DOI: 10.1007/s12021-018-9410-0
|View full text |Cite
|
Sign up to set email alerts
|

Small Animal Multivariate Brain Analysis (SAMBA) – a High Throughput Pipeline with a Validation Framework

Abstract: While many neuroscience questions aim to understand the human brain, much current knowledge has been gained using animal models, which replicate genetic, structural, and connectivity aspects of the human brain. While voxel-based analysis (VBA) of preclinical magnetic resonance images is widely-used, a thorough examination of the statistical robustness, stability, and error rates is hindered by high computational demands of processing large arrays, and the many parameters involved therein. Thus, workflows are o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 84 publications
(124 reference statements)
0
59
0
Order By: Relevance
“…Images were processed using a high-performance computing pipeline (Anderson et al, 2017(Anderson et al, , 2018a, to perform diffeomorphic mapping of a symmetric mouse brain atlas, containing 332 regions, based originally of the one presented in Calabrese et al (2015). To perform these processes we employed at the core of our pipeline advanced normalization tools (Avants et al, 2008(Avants et al, , 2011.…”
Section: Image and Network Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Images were processed using a high-performance computing pipeline (Anderson et al, 2017(Anderson et al, , 2018a, to perform diffeomorphic mapping of a symmetric mouse brain atlas, containing 332 regions, based originally of the one presented in Calabrese et al (2015). To perform these processes we employed at the core of our pipeline advanced normalization tools (Avants et al, 2008(Avants et al, , 2011.…”
Section: Image and Network Analysismentioning
confidence: 99%
“…We have implemented code for tract based analyses 2 . The tracts connecting pairs of atlas regions (Anderson et al, 2018a) were used to build connectomes based on a constant solid angle (Q-Ball method) method implemented in DIPY (Garyfallidis et al, 2014). We used a relative peak ratio of 0.5, separation angle 25 • , and 4 parallel compute threads.…”
Section: Image and Network Analysismentioning
confidence: 99%
“…Further reductions in acquisition times come from compressed sensing [28], which several groups have implemented for mouse MRI [29][30][31]. Such advances can help translate diffusion protocols into population studies [32] incorporating multiple biomarkers from morphometry [33], microstructural properties based on diffusion [13] or magnetic susceptibility [34], or network properties [35]. Such integrative studies may better predict changes in behaviors, modeling those observed in humans with neurodegenerative conditions [34].…”
Section: Discussionmentioning
confidence: 99%
“…MDT computation was performed using the script in ANTs named "antsMultivariateTemplateConstruction2.sh" with the following SyN parameters: gradient step size = 0.1 voxels, update field variance = 3 voxels, and total field variance = 0.5 voxels. These SyN parameters were suggested by a recent mouse ex vivo brain study to account for a balance between registration quality and computation time [44]. Other parameters were as follows: iteration of template creation = 4, maximum iterations for each pairwise registration = 30 × 20 × 10, shrink factors = 4 × 2 × 1 voxels, smoothing factors = 2 × 1 × 0 voxels, similarity metric = cross-correlation, radius in brackets = 4 voxels, N4BiasFieldCorrection = on, and type of transformation model = Greedy SyN.…”
Section: Minimum Deformation Templatementioning
confidence: 99%